Game Theory and the First World War - Myerson, Roger B. (Journal of Economic Literature, 2023)
Books by Scott Wolford and Roger Ransom show how economic theories of games and decisions can be fruitfully applied to problems in World War I. This vital application offers fundamental insights into the analytical methods of game theory. Public random variables may be essential factors in war-of-attrition games. An assumption that nations can coordinate on Pareto-superior equilibria may become less tenable when nations are at war. Interpreting a surprising mistake as evidence of an unlikely type can have serious consequences. The ability of leaders to foster consistent beliefs within a cohesive society can create inconsistency of beliefs between nations at war. (JEL C70, D74, D83, F51, N40)